From Agriculture to Nutrition : Pathways, Synergies and Outcomes - Hawkes, Corinna; Ruel, Marie T. (World Bank, Washington, DC, 2012)
This note discusses the direct pathways through which agricultural production can contribute to improved nutrition. It then reviews recent changes in the global environment which affect the ways in which agriculture and nutrition are linked. It concludes with a discussion of how nutrition-related objectives can be effectively incorporated into the design of agriculture programs for maximum impact on the poor.